Kemaslahatan Manusia Sebagai Puncak Maqāṣid al-Qur`ān: Tinjauan Terhadap Konsep Maqāṣid al-Qur`ān Abd al-Karīm Hāmidī - M. Fahrian Noor; Yuni Wahyuni; Bisri Samsuri (Al-Qudwah)
The article discusses the theory of maqāṣid al-Qurān conceptualized by Abd al-Karīm Hāmidī, which leads to the concept of human welfare (al-maṣlahah). There are several developments from the concepts of his predecessors, such as Rasyid Riḍa, Mahmūd Syaltūt, and Ibn Āsyūr, formulated in their concept of maqāṣid al-Qurān. Hāmidī extensively elaborates on the maqāṣid al-Qurān oriented towards the welfare of individuals, society, and nature. The discussion in this article will focus on answering two questions: first, what is the concept of maqāṣid al-Qurān according to Abd al-Karīm Hāmidī, and second, what is the purpose of maqāṣid al-Qurān in relation to maqāṣid al-syarīah. This research is a type of literature study using a descriptive-analytical method. The researcher will describe Hāmidī's thoughts on maqāṣid al-Qurān and then analyze the concept of al-maṣlahah he intended. The findings of this study show that maqāṣid al-Qurān has a hierarchy consisting of al-maqāṣid al-āmmah, which is the overall wisdom of the Qur’an covering: the goals of individual goodness, the goals of social and community welfare, and the goals of worldly goodness. Al-maqāṣid al-khāṣsah, specifically the shariah, which includes the goals of improving the mind, self, body, family, wealth, law, legislation, and politics. Then, al-maqāṣid al-juz’iyyah, meaning, and rules related to laws that stand alone, such as the goal of purification, facing the qibla, prayer times, and others. The three aspects of maqāṣid al-Qurān have one goal, which is to realize the welfare and goodness of humanity on this earth. Additionally, there is a continuity between the concept of maqāṣid al-Qur`ān proposed by Hāmidī and the concepts in maqāṣid al-syarīah formulated by Muslim scholars before him